Uji F1 dari Persilangan Genotip Antara Beberapa Varietas Kedelai (Glycine max L. Merril) Terhadap Tetua Masing-Masing - Heri Arifianto; Diana Sofia Hanafiah; Emmy Harso Kardhinata (Universitas Sumatera Utara, 2015)
This research aims to known inheritance soybean plant on F1 descent. The research was conducted at Agriculture Faculcity Universitas Sumatera Utara, Medan in June 2014 until February 2015. The research counducted in 2 phase. The first phase is crossing, are G1 (♀Detam II X ♂Anjasmoro), G2 (♀Anjasmoro X ♂Detam II), G3 (♀Grobogan X ♂Anjasmoro), G4 (♀Anjasmoro X ♂Grobogan), G5 (♀Grobogan X ♂Detam II) and G6 (♀Detam II X ♂Grobogan). The second phase is F1 test. The percentage of successfully are 32.22-46.45%. The highest result of crossing G1 and the lowest G4. G1 and G2 significantly different of flower age, plant height, number of seeds and pods with seed 1, number of seeds and pods with seed 2, number of seeds and pods with seed 3, number of pods containing, number of seed per plant, seed weight per plant and 100 seeds weight. G5 and G6 significantly different of flower age, harvesting time, primer branch number, number of seeds and pods with seed 2, number of seeds and pods with seed 3, number of pods containing, number of seed per plant and seed weight per plant. Difference between F1 and F1 reciprocal occur because of maternal inheritance inindividuals crossing result.Key words : crossing, Anjasmoro, Detam II, Grobogan, F1 test